The Front Line of Defense: Summary of the Efficacy of a Novel Intranasal Vaccine Formulation against Respiratory Threats in a Forward Deployed Military Setting - Al Hazmi, Fayza Karman Nasha; Alanazi, Amani Zaben Mashan; Hamzi, Shroq Hadi Hassan; Alamri, Khaled Mohammed; Alnami, Abdullah Talaq; Awois, Nada Ahmad; Alasam, Hussam Ali Mohammed; Alashjaee, Abdulrahman Abdullah; Almutairi, Mohammed Abdulrahman (Saudi Journal of Medicine and Public Health, 2024)
Background: Forward-deployed military troops are at high risk for acute respiratory infections (ARIs), an age-old and continuing challenge to operational readiness. Conventional intramuscular (IM) vaccines, which induce mostly systemic immunity, offer less than optimal protection at the mucosal portals of pathogen entry. Aim: This review synthesizes current evidence of the effectiveness of novel intranasal (IN) vaccine technologies against respiratory threats, with specific focus on their application in a forward-deployed military environment. Methods: A Systematic literature review was conducted in PubMed, Scopus, and Web of Science (2000-2024). Key search terms utilized were "intranasal vaccine," "mucosal immunity," "military personnel," "respiratory infection," "serological testing," and "PCR." Results: Research has demonstrated that IN vaccines, particularly the live-attenuated and adenoviral vector vaccines, have a strong mucosal immune response characterized by tissue-resident memory T-cells and secretory IgA. Such a response outperforms IM vaccines in primary infection and transmission prevention. Logistically, IN delivery has numerous advantages of deployment, including simplicity of use and absence of needles. Evaluating effectiveness requires an integrated model that combines laboratory aspects (serology and PCR) with nursing activities (administration, adverse event tracking, and disease surveillance). Conclusion: New formulations for IN vaccines possess vast potential to protect forces in the field. Their sterilizing immunity and operational benefit make them an important future asset. Success depends on an entirely integrated framework that leverages diagnostics and clinical expertise to guard force health and mission preparedness.